Assessment of Neutrophil gelatinase-associated lipocalin (NGAL) as an early biomarker for detection of renal impairment in hypertensive patients - Gharishvandi, Fatemeh; Kazerouni, Faranak; Ghanei, Esmat; Rahimipour, Ali; Amirrsouli, Houshang; Nasiri, Malihe (Archives of Advances in Biosciences, 2013)
Chronic kidney disease (CKD) is probably the most important problem of public health in advanced countries. Kidneys are often damaged as a result of high blood pressure. One of our main concerns in patients with hypertension is early detection of kidney disorders. The routine biomarkers such as creatinine have some limitation for this purpose, however recent studies suggest plasma NGAL to be a better marker. Therefor in this study we assessed the diagnostic value of plasma NGAL and compared it with serum creatinine in hypertensive patients. This study was performed on 42 hypertensive patients and 30 healthy Volunteer, both with normal serum creatinine and urea concentration who referred to Shohada Tajrish Hospital, plasma NGAL were measured subsequently using ELISA method and eGFR was considered as the gold standard method(cut off value of<78ml.min.1.73m2). mean NGAL level was significantly higher in patients in comparison to control group. The sensitivity and specificity were 96% and 100% respectively for plasma NGAL(≥32.2 ng/ml) compared with 76% and 47% for serum creatinine (>0.97 mg/dl). Our findings indicate that NGAL is a better indicator of kidney impairment in the early stages of CKD as compared with serum creatinine in hypertensive patients.